Experimental Study of Low Frequency Pulsating Liquid Jet Impingement in a confined planar geometry - Sridhar, Abishek; Narayanaswamy, Ramesh; Narayanan, V. (IIT Kharagpur, 2013)
The use of pulsating impinging jets has been found to have both enhancing as well as deteriorating heat transfer characteristics as compared to traditional steady state jets, depending on the operating conditions. Liquid jet impingement is preferred over air jets for several applications due to their substantially much larger heat transfer coefficients. While there is considerable literature on heat transfer characteristics associated with pulsating air jet impingement, that on the effect of jet pulsations for submerged liquid jet impingement cooling configurations is sparse. An experimental investigation is thus carried out to study the effect of pulsation frequency and amplitude for submerged slot jet impingement cooling of de-ionized water on a heated aluminium surface for Reynolds numbers in the range 500 - 3400, frequencies of 0.25 Hz and 0.5 Hz, and amplitudes of 50% and 100% of mean flow. In addition, steady state experiments were also carried out for 800 ≤ Re ≤ 7000 for three different jet inlet temperatures 34.83 °C, 39.68 °C and 44.54 °C. For the range of parameters studied, it was found that the effects of jet pulsations are only marginal on the time-averaged heat transfer characteristics. While the effect of jet pulsations was negligible for Reynolds numbers up to 1000, a slight decrease (up to 12%) was observed in the Nusselt number for larger Reynolds numbers with jet pulsations.